Kontribusi motivasi belajar dan penguasaan kalimat efektif terhadap keterampilan menulis teks eksposisi siswa kelas X SMA Negeri 1 Kampar - Perawati; Atmazaki; Novia Juita (Journals of Indonesian Multidisciplinary Research, 2024)
This research aims to: (1) explaining there a contribution learning motivation in the exposition text writing skills students class X SMA Negeri 1 Kampar; (2) explaining there a contribution mastery of effective sentence in the exposition text writing skills students class X SMA Negeri 1 Kampar; and (3) explaining there a contribution learning motivation and mastery of effective sentence in the exposition text writing skills students class X SMA Negeri 1 Kampar. The research sample is taken 15% of the total population of students each class are 40 students. The data of this research is from the score result of learning motivation questionnaire, the score test results mastery of effective sentence and score test result exposition text writing skills that is converted into value. The results showed that the learning motivation and mastery of effective sentences can be used as predictors to improve learning outcomes exposition text writing skills. Therefore, to increase learning outcomes writing skills, the students are given the learning motivation to write and mastery of effective sentences.